New species and color forms of Empoasca (Hemiptera: Cicadellidae: Typhlocybinae: Empoascini) from South America - Southern, Phillip Sterling (Zootaxa, 2008)
Three new Neotropical species in the genus Empoasca are described and illustrated (Empoasca bartletti n. sp., Empoasca concava n. sp., Empoasca coofa n. sp.). The species are placed in a previously published key and relationships to other species of the genus are described. Two informal species groups, the E. dolonis group and the E. papae group are described and included species are listed. Evidence for the occurrence of dimorphic color forms in the genus is discussed.